Same, but different: Testing monetary policy shock measures - Stephanie Ettmeier; Alexander Kriwoluzky (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
In this study, we test whether three popular measures for monetary policy, that is, Romer and Romer (2004), Barakchian and Crowe (2013), and Gertler and Karadi (2015), constitute suitable proxy variables for monetary policy shocks. To this end, we employ different test statistics used in the literature to detect weak proxy variables. We find that the measure derived by Gertler and Karadi (2015) is the most suitable in this regard.
urn:nbn:de:gbv:3:2-71302
Keywords: C12; C32; E32; E52; 330; monetary policy shock measures; Proxy-SVAR; weak proxies; F-test